Making Sense Together: The Intersubjective Approach to Psychotherapy - Buirski, Peter; Haglund, Pamela; Markley, Emily (Rowman & Littlefield Publishers, 2020)
The second edition of Making Sense Together provides a greater examination of the clinical practice of the intersubjective perspective. Listening and responding intersubjectively is concerned with attuning to affect, putting words to affective experience, and maintaining a caring relationship that offers the kind of needed self-objective experience missing in development. In addition, the intersubjective perspective co-constructs a developmental narrative that contextualizes the evolution of the person’s troubles. In this new and updated edition, authors Peter Buirski, Pamela Haglund, and Emily Markley draw on more than twenty years of combined experience teaching and supervising in the practice of the intersubjective perspective.